Using Structural Data to Indicate the Folding Type of Anticlines Examples from the Kurdistan Region, Iraq - Sissakian, Varoujan K.; Abdullah, Lanja H. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2025)
Using seismic data is the most relevant and sound method to indicate the folding type in anticlines. However, when seismic data are not available or not allowed for use, then structural data are recommended to indicate the folding type of any anticline. Such usage is known and considered worldwide with excellent results. We have adopted a sound and published opinion of using structural data to indicate the folding type, and applied the method on three anticlines, namely, Qara Boutaq, Korek, and Mateen. We have selected the three anticlines from three different tectonic zones in the Iraqi Kurdistan Region, which is located in the northern and northeastern parts of Iraq, and forms the northeastern part of the Arabian Plate. The plate has been colliding with the Eurasian Plate since the Late Cretaceous and is still in collision; accordingly, all the existing anticlines are developed. We used satellite images to measure the required structural parameters, including aspect ratio, fold symmetry index, and Mountain Front Sinuosity Index in these anticlines. We also measured the dip amounts along the three anticlines from satellite images, where there are no dip measurements in the geological maps, to indicate the geometrical type of the three anticlines. Part of the interpreted data was checked and confirmed in the field, wherever it was accessible. Accordingly, we indicated the folding type to be Detachment Fold for the Qara Boutaq and Korek anticlines and Fault-bent Fold for the Mateen anticline.